A raspberry pi-based solution for high-frequency acquisition and transmission of measured data (2021)
Modern measurement and process automation solutions are of vital importance within the current context of industry 4.0. It is required to develop efficient, effective, and even low-cost alternatives. In this document, the Raspberry Pi is presented as a small but powerful computer, capable of performing multiple functions within a general process of remote data acquisition and sending to an online server. Then, a particular case study is explained, in which a specific sensor is used as a source of measured data from a Raspberry Pi, and then sent to a web application developed specifically to host data samples. All the above was done after an extensive theoretical analysis of the scope and limitations of the Raspberry Pi and the other elements concerning the designed process flow.